Resgate vegetativo e propagação via estaquia e miniestaquia de Toona ciliata M. Roem. var. australis (F. Muell.) Bahadur - Pereira, Mariane de Oliveira (2014)
Orientador : Prof. Dr. Antonio Carlos Nogueira